Determinants Of Tourism Network Success - CHYAW IN, JULIE BOEY (2005)
The purpose of this study is to investigate the characteristics of the succesful collaborative networking in Penang tourism industry, and the effect of these factors on the network performance in the form of business and organizational performance. The factors selected under this study are trust, commitment, communication, information sharing and perceived conflict.